SAT0223 Indirect comparative clinical effectiveness of intravenous and subcutaneous formulations of belimumab for the treatment of adult patients with active, autoantibody-positive systemic lupus erythematosus with high disease activity. (15th June 2017) - Parks, D; Ramachandran, S; Kurtinecz, M; Asukai, Y; Alfonso-Cristancho, R
Abstract : Background: The efficacy of belimumab (BEL) vs placebo (PBO), in adult patients with active, autoantibody-positive systemic lupus erythematosus (SLE) who are receiving standard SLE therapy has been demonstrated. To date, no direct comparison of intravenous (IV) BEL vs subcutaneous (SC) BEL has been performed, hence the importance of an indirect treatment comparison (ITC). Objectives: To indirectly compare the clinical effectiveness of BEL IV and SC formulations in patients with SLE high disease activity (HDA) via an ITC. Methods: Three BEL IV Phase lll randomised controlled trials (RCTs; HDA/BLISS-52, 327/577; HDA/BLISS-76, 265/548; HDA/North East Asia study [BEL113750], 427/677) and one BEL SC RCT (HDA/BEL112341; 356/836) were compared via a Bayesian ITC (BEL207255). We evaluated the relative efficacy of the formulations in patients meeting three measures of HDA at baseline (1. BLISS-52 and BLISS-76, C3 <0.9 g/L or C4 <0.16 g/L; BEL112341 and BEL113750, C3 <0.9 g/L or C4 <0.10 g/L; and 2. anti-dsDNA positive [≥30 IU/mL] or 3. Safety of Estrogen in Lupus Erythematosus National Assessment-SLE Disease Activity Index [SELENA-SLEDAI] scores ≥10). Analyses were conducted in patients meeting Criteria 1: low C3/C4 and high anti-dsDNA; and Criteria 2: low C3/C4 and high anti-dsDNA or SELENA-SLEDAI ≥10 or low C3/C4. The primary endpoint was SLE Responder Index (SRI) response (≥4-point reduction in SELENA-SLEDAI, no worsening in Physician's Global Assessment, no new 1A/2B British Isles Lupus Assessment Group domain scores) at Week 52. Secondary endpoints included ≥4-point reduction in SELENA-SLEDAI and SLE Flare Index rate. Safety endpoints were not assessed. Results: Baseline characteristics were relatively similar between RCTs and a fixed effects model binomial distribution with logit link was used for all efficacy endpoints (Table). In this indirect comparison, no differences were identified between BEL IV and BEL SC for the efficacy endpoints. Conclusions: In this indirect comparison, BEL IV and BEL SC were similar for SRI response, ≥4-point reduction in SELENA-SLEDAI, or rate of severe flare at Week 52 in patients with SLE. Outcomes were consistent irrespective of the criteria applied. Acknowledgements: Study funded by GSK. Katie White, PhD, Fishawack Indicia Ltd, UK, provided editorial assistance funded by GSK. Disclosure of Interest: D. Parks Shareholder of: GSK, Employee of: GSK, S. Ramachandran Shareholder of: GSK, Employee of: GSK, M. Kurtinecz Employee of: GSK, Y. Asukai Shareholder of: GSK, Employee of: GSK, R. Alfonso-Cristancho Shareholder of: GSK, Employee of: GSK